Akurasi Penggunaan Chat GPT dalam Menganalisis Materi Pembelajaran Pendidikan Agama Buddha - Aprilisa Pratiwi; Partono Partono; Suherman Suherman (Jurnal Budi Pekerti Agama Buddha, 2024)
Information technology refers to any technology that assists human needs. Advances in computing and information technology significantly impact education through the use of computer networks and the internet. Artificial Intelligence (AI) is one of the most beneficial applications across various fields, including healthcare, industry, governance, and particularly in education, as exemplified by ChatGPT (Chat Generative Pre-Trained Transformer). This study focuses on the accuracy of ChatGPT in analyzing learning materials for Buddhist Religious Education. It not only examines the technological accuracy but also explores its potential as an effective learning tool in formal educational settings. The method employed is a literature review, aiming to investigate the accuracy of ChatGPT in educational contexts. This research seeks to evaluate ChatGPT's capability to analyze materials and provide precise answers. However, as ChatGPT continues to evolve, there is a risk of increasing student dependency on its use. Despite its advantages, ChatGPT also has limitations, such as its reliance on available data.